The Urgention of Use of Technology as A Minute Protection of Notary Assets That are Lost or Damaged Due to Natural Disasters - Mohammad Rizal Zulkifli Ramli (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
This study aims to: to determine how important the application of technology is to protect the minuta notary deeds that are lost or damaged by natural disasters. The approach method in this research is sociological empirical research which is a qualitative research based on primary data. Primary data is data that is obtained directly by the object. Based on the results of data analysis, it can be concluded that the use of technology as an effort to protect notary deeds that are lost or damaged due to natural disasters has not obtained a clear legal basis because the Notary Position Law or other legal provisions do not clearly regulate the procedure for keeping the minimum deed, so that notaries do not have standard rules regarding procedures. How to keep the minuta deed, which results in not providing legal certainty and legal protection for the parties concerned. Along with the development of technology, technology should be used in order to support work, including notaries, storing minuta deeds in the form of soft files to make backup files that can be used if one day a natural disaster occurs which results in the loss or damage of a minimum certificate. The absence of a clear legal basis that regulates the use of technology as a means of storing minimum deeds is one of the obstacles to the use of technology, even though this is done to improve the performance of notaries who are an extension of the government in the field of civil law in terms of services to the public. The potential for disasters or things beyond human capacity that can cause the loss or damage of the deed as part of the notary protocol is very large, so it is necessary to make preventive efforts by the notary in carrying out one of its obligations as mandated in the UUJN. Notaries must take the initiative in keeping the minimum deeds so that their storage is completely safe and not stuck with the old habit of storing notary protocols in a cupboard or vault that is still lost or damaged due to natural disasters or other things beyond human ability. So that efforts to utilize technology should become an internal habit in the notary office while waiting for a clear legal basis.